The structure of models of Peano arithmetic - Kossak, Roman, 1953-; Schmerl, J. H. (James Henry), 1940-; Oxford eBooks (Oxford : Clarendon, 2006)
Aimed at graduate students, research logicians and mathematicians, this text covers over 40 years of work on relative classification theory for non-standard models of arithmetic.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Peano, Giuseppe, -- 1858-1932.; Logic, Symbolic and mathematical; Logic, Symbolic and mathematical -- Problems, exercises, etc; Isomorphisms (Mathematics); Isomorphisms (Mathematics) -- Problems, exercises, etc; Electronic books